A prediction method for the service trajectory of badminton moving video based on fuzzy clustering algorithm. (10th June 2021) - Zhu, Lin
Due to the weak regularity of target's motion attitude in badminton video, the existing methods cannot segment the image accurately, which leads to the low accuracy of predicting the service track of badminton video. A method of predicting the service track of badminton based on fuzzy clustering algorithm is proposed. The fuzzy clustering algorithm is used to segment the video image of badminton movement, obtain the contour of the serving arm in the video image, calculate the body state ratio and compactness of the serving arm of the moving object, construct the overall matching similarity function of the moving object, and realise the tracking and trajectory prediction of the moving object in the video image. The experimental results show that the proposed method has good noise iteration performance, clearer target of the processed motion video image, and can accurately predict the serve trajectory in the badminton motion video.